Angiografia cerebral em cães (Canis familiaris) - Veiga, Denise de Castro (2005)
Cerebral angiography is radiological procedure to demonstrate areas of the vascular supply of the brain through the injection of a positive contrast where proper visualization of the blood stream is obtained. In this experiment, twenty adult dogs were submitted to a cerebral angiography. In the operation room, under general anesthesia, the left carotid artery was exposed and catheterized. The animals were then conducted to the Veterinary Radiological Sector for the cerebral angiography procedure. When good quality images where obtained, positive contrast was administrated and new x-rays were taken. The aim of this study was to evaluate this technique as a alternative radiographic technique in cases where alteration of the blood stream by occupying space such as may brain damages occure. The technique used was effective to obtain clear images, when determining the irrigation area of the brain.